PERHITUNGAN BIAYA PRODUKSI LEMARI KACA PADA UD. RUDINA SAMARINDA - Yani, Sutri (EKONOMIA, 2012)
Calculation of production cost is a calculation of a company's costs to process raw materialsinto finished goods, the industrial company consisting raw materials costs, labor costs and factory overhead costs. Probelms in this study is whether the calculation of production costs on UD. RUDINA cabinets are approprite based on the theory of production costs.Purpose of this study to determine the production cost calculation by UD. RUDINA cabinets are appropriate based on the theory of production costs.Based on the analysis and discussion, the calculation of this study received the following reasons : Calculation of production costs in UD. RUDINA not apprapriate based on the theory of production cost because the system is applied to the calculation UD. RUDINA inaccurate because the company did not calculate the cost of factory overhead while in the calculation of the production costs consists of the cost of raw materials, labor costs and factory overhead costs.